2019
DOI: 10.3390/su11082405
|View full text |Cite|
|
Sign up to set email alerts
|

Perception and Preference Analysis of Fashion Colors: Solid Color Shirts

Abstract: When it comes to pollution, we do not usually think about the clothes we wear, but the clothing industry is really endangering our planet. The market economy has transferred the decision-making power of the garment industry from enterprises to consumers. To make the fashion industry sustainable, in addition to technological innovation, it is also necessary to conduct research on the service objects of the industry. Consumer clothing preference research is an important part of the sustainable development of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The color perception process usually causes related feelings or emotions in individuals' brains [39]. This perception or emotion affects consumers' color preferences and can be used to predict their behavioral intention [37].…”
Section: Colormentioning
confidence: 99%
“…The color perception process usually causes related feelings or emotions in individuals' brains [39]. This perception or emotion affects consumers' color preferences and can be used to predict their behavioral intention [37].…”
Section: Colormentioning
confidence: 99%
“…K and Kon (2.48), two of the most unfavourable indigo colour shades, are both colours, the latter of which is close to black, suggesting that indigo colours in t blue range were more favoured among the subjects. For Application, since th match/easy-to-match", a key factor influencing consumer's buying behavior, to be closely related to the "dislike/like" preference [25], this study's results m aged to increase consumers' willingness to buy.…”
Section: Discussionmentioning
confidence: 94%
“…An associative learning framework can be used to explain human physiological response to colour [24]. Jiang, Chen and Zhang demonstrated that the "hard-to-match/easy-to-match" response, a determining factor for consumers' willingness to buy, was found to be highly correlated with "dislike/like" [25]. In the late 1970s, a study conducted at UCLA (University of California, Los Angeles) revealed that when looking at the colour blue, subjects have lower blood pressure, show reduced brain wave activity, breathe slower, and sweat less.…”
Section: Colour Preference and Associationmentioning
confidence: 99%
“…But un-fortunately, some of these technologies had a negative impact on the environment and thus prompted the emergence of green institutions, the dissemination of a culture of sustainability for a secure future, and a call for preserving the earth and its natural resources. Balconi et al [1] and Jiang et al [2] have confirmed that the garment industry is the second largest polluting industry for the environment, starting from the manufacturing cycle to the consumption and disposal of garments. Therefore, many fashion institutions, such as the Dutch C & A 1 , took the initiative to use bio-cotton in the manufacturing of their products.…”
Section: Introduction and The Research Problemmentioning
confidence: 97%
“…It has also launched a program to collect old garments and recycle them. In 2017, C & A received the C2CTM 2 certificate, and now it has more than 4 million certified pieces of garments. Meanwhile, New Balance USA for Sporting Goods 3 started to take great strides toward the preservation of the environment by recycling polyester, which subsequently resulted in lower carbon emissions and energy consumption.…”
Section: Introduction and The Research Problemmentioning
confidence: 99%